Housing Environmental Risk in Urban Areas: Cross Country Comparison and Policy Implications - Bruno Chiarini; Antonella D'Agostino; Elisabetta Marzano; Andrea Regoli (Center for Economic Studies and ifo Institute (CESifo), 2017)
The main aim of this paper is to assess whether there is a statistically significant environmental impact of cities within European countries. Second, starting from the estimated environmental impact of cities within European countries, the paper investigates whether cross-country variation can be explained by macro-economic factors and government policies which can play a role in mitigating such an impact. We start from individual evidence (EU-SILC data) to obtain a measure of the environmental impact of cities within countries, and then correlate the latter with macro variables to explain European heterogeneity. These estimates confirm that the environmental risk for households is particularly perceived in more densely populated urban agglomerations, although the marginal effects are quite heterogeneous between countries. Macroeconomic factors such as inequality, wealth, taxation and public spending on the environment, and macroeconomic constraints such as the public finance disequilibrium produce a strong heterogeneity between countries in determining the marginal effects of urban metropolises on household environmental risk.
Keywords: Q51; Q53; R21; I31; C35; 330; household environmental risk; sustainable cities; bivariate probit model; cross-country heterogeneity